The CD63 homologs, Tsp42Ee and Tsp42Eg, restrict endocytosis and promote neurotransmission through differential regulation of synaptic vesicle pools - Hendricks, Emily L.; Smith, Ireland R.; Prates, Bruna; Barmaleki, Fatemeh; Liebl, Faith L. W. (Frontiers in Cellular Neuroscience, 2022)
The Tetraspanin (Tsp), CD63, is a transmembrane component of late endosomes and facilitates vesicular trafficking through endosomal pathways. Despite being widely expressed in the human brain and localized to late endosomes, CD63’s role in regulating endo- and exocytic cycling at the synapse has not been investigated. Synaptic vesicle pools are highly dynamic and disruptions in the mobilization and replenishment of these vesicle pools have adverse neuronal effects. We find that the CD63 homologs, Tsp42Ee and Tsp42Eg, are expressed at the Drosophila neuromuscular junction to regulate synaptic vesicle pools through both shared and unique mechanisms. Tsp42Ee and Tsp42Eg negatively regulate endocytosis and positively regulate neurotransmitter release. Both tsp mutants show impaired locomotion, reduced miniature endplate junctional current frequencies, and increased endocytosis. Expression of human CD63 in Drosophila neurons leads to impaired endocytosis suggesting the role of Tsps in endocytosis is conserved. We further show that Tsps influence the synaptic cytoskeleton and membrane composition by regulating Futsch loop formation and synaptic levels of SCAR and PI(4,5)P2. Finally, Tsp42Ee and Tsp42Eg influence the synaptic localization of several vesicle-associated proteins including Synapsin, Synaptotagmin, and Cysteine String Protein. Together, our results present a novel function for Tsps in the regulation of vesicle pools and provide insight into the molecular mechanisms of Tsp-related synaptic dysfunction.